2003
DOI: 10.3168/jds.s0022-0302(03)73597-8
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Milk Production and Antibody Response to Ovalbumin During the Peripartum Period

Abstract: Suboptimal innate and immune mechanisms of host resistance during the peripartum period may contribute to increased incidence of mastitis. To evaluate associations between antibody response to ovalbumin and milk production during the peripartum period, 136 Holstein cows and heifers from three herds with known antibody response profiles, were evaluated for projected 305-d milk, protein, and fat yield. Using a previously described index (Wagter et al., 2000), cows were quantitatively classified based on their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Initial studies of antibody-mediated immune response (AMIR) and cellmediated immune response (CMIR) as indicators of improved host defense were carried out on mice (Biozzi et al, 1979), chickens (Pinard et al, 1992), and pigs (Mallard et al, 1992). Subsequent examination of dairy cows indicated that there is sufficient genetic variation between animals within a breed to allow breeding for AMIR and CMIR (Wagter et al, 2003). In 2 out of 3 herds tested during the periparturient period, there were lower incidences of mastitis and other diseases in high antibody responders (Wagter et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies of antibody-mediated immune response (AMIR) and cellmediated immune response (CMIR) as indicators of improved host defense were carried out on mice (Biozzi et al, 1979), chickens (Pinard et al, 1992), and pigs (Mallard et al, 1992). Subsequent examination of dairy cows indicated that there is sufficient genetic variation between animals within a breed to allow breeding for AMIR and CMIR (Wagter et al, 2003). In 2 out of 3 herds tested during the periparturient period, there were lower incidences of mastitis and other diseases in high antibody responders (Wagter et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent examination of dairy cows indicated that there is sufficient genetic variation between animals within a breed to allow breeding for AMIR and CMIR (Wagter et al, 2003). In 2 out of 3 herds tested during the periparturient period, there were lower incidences of mastitis and other diseases in high antibody responders (Wagter et al, 2003). Heritability estimates of 0.37 and 0.41 have been reported for AMIR and CMIR, respectively (Hernandez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Production measures are significantly affected by parity. This is similar to results in other reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, selection of pigs for both H AMIR and CMIR indicates health and production benefits [8]. A recent study of cows during the peripartum period also suggests benefits to individuals with H antibody responsiveness [22]. To refine and improve this index, a simple, safe, and effective means was sought to induce both AMIR and CMIR for classifying H and L responders.…”
Section: Discussionmentioning
confidence: 99%